2013
DOI: 10.1074/mcp.m112.024661
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium Urate Activates Src/Pyk2/PI3 Kinase and Cathepsin Dependent Unconventional Protein Secretion From Human Primary Macrophages

Abstract: Monosodium urate (MSU) is an endogenous danger signal that is crystallized from uric acid released from injured cells. MSU is known to activate inflammatory response in macrophages but the molecular mechanisms involved have remained uncharacterized. Activated macrophages start to secrete proteins to activate immune response and to recruit other immune cells to the site of infection and/or tissue damage. Secretome characterization after activation of innate immune system is essential to unravel the details of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 69 publications
2
38
0
Order By: Relevance
“…Recent system level characterizations using modern mass spectrometrybased proteomics approaches have provided important novel information how innate immune cells, including macrophages, activate much more global protein secretion than just secreting cytokines and chemokines and that this global protein secretion is an important part of the innate immune response to different activation stimuli. We have previously shown that activators of canonical NLRP3 inflammasome, including monosodium urate and ATP, induce robust unconventional vesicle-mediated protein secretion in human macrophages (19,20). Our present results show that also non-canonical caspase-4/5 inflammasome activates EV-mediated protein secretion in human macrophages.…”
Section: Caspase-4/5 Inflammasome-activated Protein Secretionsupporting
confidence: 71%
See 3 more Smart Citations
“…Recent system level characterizations using modern mass spectrometrybased proteomics approaches have provided important novel information how innate immune cells, including macrophages, activate much more global protein secretion than just secreting cytokines and chemokines and that this global protein secretion is an important part of the innate immune response to different activation stimuli. We have previously shown that activators of canonical NLRP3 inflammasome, including monosodium urate and ATP, induce robust unconventional vesicle-mediated protein secretion in human macrophages (19,20). Our present results show that also non-canonical caspase-4/5 inflammasome activates EV-mediated protein secretion in human macrophages.…”
Section: Caspase-4/5 Inflammasome-activated Protein Secretionsupporting
confidence: 71%
“…These cells are much more heterogeneous starting material than cell lines. We have seen this in our previous studies (19,29), and here these differences manifest in quantification fold differences obtained from different biological replicates.…”
Section: Non-canonical Inflammasome Activates Ev-mediated Protein Secsupporting
confidence: 56%
See 2 more Smart Citations
“…Macrophages are among the key cells that rapidly respond to and coordinate the local inflammatory response to MSU crystals (5)(6)(7)(8)(9)(10). Cells of the monocyte/macrophage lineage are highly dynamic immune cells that readily alter their functional phenotype in response to the local inflammatory environment and in a stimulus-specific manner (11,12).…”
mentioning
confidence: 99%